Does Indian real estate regulation protect urban homebuyers? policy implications - Neelam Chawla; Basanta Kumar (Cogent Business & Management, 2022)
The proponents claim that the Indian Real Estate (Regulation and Development) Act, 2016 (RERDA, 2016/Act) has saved homebuyers from exploitation by promoters' evasive and aggressive approach and has impacted society. The paper, while discussing the relevant statutory provisions and judicial decisions protecting urban homebuyers' interests, examines the reactions of 751 respondents, comprising homebuyers, unsuccessful buyers, builders, officials, and nine experts, using descriptive statistics, ANOVA, and the chi-square test. The findings show that builders' lobbying and regulatory capture exploit homebuyers. Timely judiciary interventions have eased builders' obstacles, allowing builders and governments to safeguard homebuyers' interests. Politics and interstate tensions create homebuyers' owes. Violation of ethical principles is a common practice. However, the Act's performance remains uneven six years after its adoption. Our results on real estate reform might help policymakers, and planners, alter current laws in a worldwide competitive economy. Our findings suggest that a law's success in a country's development depends on political will, design, alignment with development objectives, flexibility, efficacy, and adaptability to socioeconomic realities. The study has implications for research on the real estate market's theory, policy, and socioeconomic practice.
Keywords: 650; builder; cities; homebuyers; real estate; RERA; RERDA